Personal Pronouns in American Presidential Political Discourse - Muhammad Masqotul Imam Romadlani (Indonesian Journal of EFL and Linguistics, 2021)
This research examines first-person personal pronouns which arise in political speeches given by Obama in his victory as American President in 2008 and 2012. Employing qualitative and quantitative methods, this research explores the occurrences of first personal pronouns to reveal the forms and its discourse function through political speeches. Abstracting from 458 personal pronouns found in Obama’s speeches, 272 pronouns are identified as first personal pronouns. The findings of the first personal pronouns employed in Obama speeches illustrated that Obama produced pronoun we and its variants, 183 times, and pronoun I and its variants, 89 times. Obama exploited singular personal pronoun to convey personally his deep appreciation and gratefulness, personal experiences, personal professional experiences, his personal argumentative opinions, hopes, and his commitment as well. The use of inclusive we and its variants indicate Obama’s desire to shares responsibility and construct nationalistic spirit, togetherness, equality, publicly assertion about the political situation, and any challenges they probably face in the future. Additionally, by employing exclusive we, Obama asserts his political plans, commitment, political experiences during the election, and serious concern of reconciliation.